2014
DOI: 10.3928/23258160-20141118-04
|View full text |Cite
|
Sign up to set email alerts
|

OCT Angiography in Healthy Human Subjects

Abstract: OCTA generates high-resolution, noninvasive angiograms qualitatively similar to conventional fluorescein angiography. OCTA may serve as a bridge to assess some features of the retinal microvasculature between conventionally performed angiograms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
176
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(188 citation statements)
references
References 22 publications
3
176
0
9
Order By: Relevance
“…It is still, however, an extremely useful tool in the diagnosis of active lesions. Newer technologies, namely the OCT angiography (OCTA) which is minimally invasive and quick could be the next step forward towards quicker, non-invasive and showing accurate vascular detail [9][10][11]. Various studies have shown that OCTA shows high specificity in the diagnosis of CNV compared to FFA [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…It is still, however, an extremely useful tool in the diagnosis of active lesions. Newer technologies, namely the OCT angiography (OCTA) which is minimally invasive and quick could be the next step forward towards quicker, non-invasive and showing accurate vascular detail [9][10][11]. Various studies have shown that OCTA shows high specificity in the diagnosis of CNV compared to FFA [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Using by OCTA, the vasculature and blood flow of retina and choroid can be visualized in detail through detecting motion contrast of erythrocytes in the vessel, using serial optical coherence tomography B-scans. OCTA has an ability to perform the separate segmentations including the vitreoretinal interface (VRI), the superficial retinal layer, the deep retinal layer, avascular outer retina (AOR), the choriocapillaris and the choroid (Figure 1) [1][2][3][4][5][6][7][8].…”
Section: Editorialmentioning
confidence: 99%
“…Using by OCTA, the vasculature and blood flow of retina and choroid can be visualized in detail through detecting motion contrast of erythrocytes in the vessel, using serial optical coherence tomography B-scans. OCTA has an ability to perform the separate segmentations including the vitreoretinal interface (VRI), the superficial retinal layer, the deep retinal layer, avascular outer retina (AOR), the choriocapillaris and the choroid (Figure 1) [1][2][3][4][5][6][7][8].In a healthy eye, the VRI has no vascular structure though the ganglion cell layer of the retina has the superficial retinal capillary plexus based on vitreo-retinal histology and VRI segmentation of OCTA (Figure 1, VRI) [1][2][3][4][5][6][7][8]. Preretinal neovascularization (PNV) is characterized by networks of vessels lying on the surface of the retina and invading the cortical vitreous gel and extending into the vitreous cavity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…OCTA is a non-invasive, non-dye-based imaging technique that employs motion contrast to create high-resolution depth-resolved angiographic images of vascular flow in a matter of minutes. [1][2][3] The software compares the decorrelation signal or phase variance between consecutive OCT B-scans acquired at the same retinal cross-section to detect motion contrast. [4][5][6] Multiple OCTA image artifacts may affect image quality.…”
mentioning
confidence: 99%